2019
DOI: 10.3758/s13414-019-01842-0
|View full text |Cite
|
Sign up to set email alerts
|

Media multitasking, mind-wandering, and distractibility: A large-scale study

Abstract: Previous studies suggest that frequent media multitaskingthe simultaneous use of different media at the same timemay be associated with increased susceptibility to internal and external sources of distraction. At the same time, other studies found no evidence for such associations. In the current study, we report the results of a large-scale study (N=261) in which we measured media multitasking with a short media-use questionnaire and measured distraction with a change-detection task that included different nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 53 publications
1
26
0
1
Order By: Relevance
“…Heavier media multitasking was associated with increased problems related to memory. In this regard, one study using an objective measure, namely a change-detection task has shown that HMMs had difficulties retaining specific information in working memory, regardless of the presence of distractors, and importantly, they performed more poorly in a later longterm memory test for both relevant and irrelevant objects compared to LMMs (Uncapher et al, 2016; but see Wiradhany, van Vugt, & Nieuwenstein, 2019 for null results). Other studies have shown that HMMs, compared to LMMs performed worse in a complex working memory test (Sanbonmatsu et al, 2013) and an N-back test (Cain et al, 2016;Ophir et al, 2009;Ralph & Smilek, 2016; but see Cardoso-Leite et al, 2015;Wiradhany & Nieuwenstein, 2017 for null results).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavier media multitasking was associated with increased problems related to memory. In this regard, one study using an objective measure, namely a change-detection task has shown that HMMs had difficulties retaining specific information in working memory, regardless of the presence of distractors, and importantly, they performed more poorly in a later longterm memory test for both relevant and irrelevant objects compared to LMMs (Uncapher et al, 2016; but see Wiradhany, van Vugt, & Nieuwenstein, 2019 for null results). Other studies have shown that HMMs, compared to LMMs performed worse in a complex working memory test (Sanbonmatsu et al, 2013) and an N-back test (Cain et al, 2016;Ophir et al, 2009;Ralph & Smilek, 2016; but see Cardoso-Leite et al, 2015;Wiradhany & Nieuwenstein, 2017 for null results).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with its counterpart in objective tasks, where studies have found that HMMs performed worse in tasks in which they have to respond to different cue-probe contingencies, such as the AXE-CPT task (Ophir et al, 2009;Wiradhany & Nieuwenstein, 2017; but see Cardoso-Leite et al, 2015 for null results). However, there were mixed findings with regard to performance of HMMs in a change-detection task in which distractor filtering was involved, with one study showed that HMMs performed worse (Ophir et al, 2009), while other, recent ones showed null findings (Cardoso-Leite et al, 2015;Uncapher et al, 2016;Wiradhany & Nieuwenstein, 2017;Wiradhany et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Research in experimental psychology found strong evidence that interest [ 33 ], task difficulty, emotional state [ 1 , 9 ], monotone or highly atomized tasks [ 24 ], and distractibility [ 34 , 35 ] are strong determinants of mind wandering. Episodes of mind wandering can also arise from semantic stimulus processing if the stimulus evokes memories [ 32 , 36 ].…”
Section: Triggers Of Mind Wanderingmentioning
confidence: 99%
“…Learners should, for example, know how to adapt their learning strategies when learning from hypermedia versus when learning from a traditional textbook or when learning in a face-to-face versus MOOC environment (Wong et al 2019). Moreover, they should learn how to manage distractions and avoid multi-tasking (Wiradhany et al 2019). However, the requirements of effective management of the information processing load go even further.…”
Section: Introductionmentioning
confidence: 99%